“MENMOZHI” Voice Perception Wheel Chair for Disabled People - Banumathi.A.C, Dr. E.Chandra,Dr. D. Sumathi (International Journal of Advanced Science and Technology, 2020)
Speech Recognition has become inevitable for this day modern era Devices. The Physically disabledpeople are assisted with a Wheel chair which operates with voice perception. Our proposed designperceives the command to be given in Tamil grammar–based recognition unit called “Menmozhi” whichmeans soft spoken in Tamil Language. The user can give various tamil commands like “Munnadisel”,“PinnadiSel”. There are two different types of command given to the wheel chair, firstly single TamilPhoneme words and to make it move to short distance inside the room and another is to give continuousTamil Phoneme words to interact with outside world (Internet). We have achieved a successful speechRecognition rate by Menmozhiup to 99.67% for movement commands and 97.12 % for Internet usage.